1980
DOI: 10.1016/s0072-968x(80)80012-x
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented Villonodular Synovitis of the Hand

Abstract: A series of fifty one lesions arising in the hand is reviewed. Fifty nine per cent of the lesions arose from the joints of the hand which are also frequently the site of degenerative changes. Twenty five per cent of available radiographs also showed such changes. The aetiology and diagnosis of this condition, the treatment and the results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 15 publications
0
8
0
3
Order By: Relevance
“…Other authors agree with an aggressive approach to reduce recurrence. 20 Applying this knowledge will hopefully allow us and others to better understand and treat giant cell tumor.…”
Section: Recurrence Of Giant Cell Tumors In the Handmentioning
confidence: 99%
“…Other authors agree with an aggressive approach to reduce recurrence. 20 Applying this knowledge will hopefully allow us and others to better understand and treat giant cell tumor.…”
Section: Recurrence Of Giant Cell Tumors In the Handmentioning
confidence: 99%
“…Histologically, its cellularity and mitotic activity have been reported to be related to recurrence (Rao and Vigorita, 1984;Wright, 1951), but this is controversial (Al-Qattan, 2001;Fyfe and Macfarlane, 1980;Jones et al, 1969;Monaghan et al, 2001;Moore et al, 1984). The cellularity and number of mitotic figures found in this tumour vary (Monaghan et al, 2001;Rao and Vigorita, 1984;Wright, 1951) with some localized GCTTS having a high proliferative activity.…”
Section: Introductionmentioning
confidence: 96%
“…In a report by Moore et al , no bone destruction was found among 115 cases of GCTTS ( 9 ). Bone destruction was detected in only 1 out of 51 cases of GCTTS reported by Fyfe and MacFarlane ( 10 ). Jones et al ( 11 ) studied 91 cases of GCTTS in the hand, among which 11 cases showed evidence of cortical bone erosion without bone destruction.…”
Section: Discussionmentioning
confidence: 94%